Safety and efficacy of lumefantrine-artemether (Coartem®) for the treatment of uncomplicated Plasmodium falciparum malaria in Zambian adults - Mulenga Modest; Van geertruyden Jean-Pierre; Mwananyanda Lawrence; Chalwe Victor; Moerman Filip; Chilengi Roma; Van Overmeir Chantal; Dujardin Jean-Claude; D'Alessandro Umberto (Malaria Journal, 2006)
Abstract Background In Zambia, unacceptably high resistance to commonly used antimalarial drugs prompted the choice of artemether-lumefantrine (AL) as first line treatment for uncomplicated Plasmodium falciparum malaria. Although the safety and efficacy of AL have been extensively documented, no clinical trials had been carried out in Zambia. Methods Nine hundred seventy one adult patients with uncomplicated malaria were randomized to either sulfadoxine-pyrimethamine (SP)(486) or AL (485) and followed up for 45 days. Outcome of treatment was defined according to the standard WHO classification. Recurrent parasitaemia were genotyped to distinguish between recrudescence and new infection. Results Fever at day 3 was significantly lower (AL: 0.9%; 4/455; SP: 3,5%; 15/433; p = 0.007) and the mean haemoglobin at day 45 significantly higher (AL: 134 g/l; SP 130 g/l; p = 0.02) in the AL group. Almost all clinical symptoms cleared faster with AL. Early treatment failure was significantly higher in the SP (25/464) than in the AL (2/463) (OR: 13.1 95% CI: 3.08–55.50; P < 0.001). The rate of new infections was similar in both groups (18 with SP and 19 with AL). Late clinical failure (OR: 2.55; 95% CI: 1.34–4.84; P = 0.004) and late parasitological failure (OR:3.18; 95% CI: 1.25–8.09; P = 0.02) were significantly higher in the SP group. Total treatment failure was significantly higher in the SP group (96/393; 19.3%) as compared to the AL (22/403; 5.4%) group (OR: 4.15; 95% CI: 2.52–6.83; P < 0.001). Conclusion In Zambia, the new first line regimen AL is far more efficacious than SP in treating uncomplicated P. falciparum malaria in adults. Data on safety and efficacy of AL in pregnant women are urgently needed.